Performativity, regulative fictions, huge stabilities: framing battered woman's syndrome - T. Threadgold (Law Text Culture, 1997)
I want in this paper to explore the stories that proliferate around the lived narrative realities of women who kill violent husbands. I will even tell some more stories but I do this in the knowledge that not just any stories will do. As Graycar (1996) has argued there are very real limits to the perfonnative power of feminist narratives if they fail to engage with the huge stabilities, legal discipline, categories doctrines and, I would add, practices, that they are attempting to change.